Innovations in digital research methods - Halfpenny, Peter, Comp; Procter, Rob, Comp (Sage Publications Ltd, 2015)
Vast amounts of digital data are now generated daily by people as they go about their lives, yet social researchers are struggling to exploit it. At the same time, the challenges faced by society in the 21st century are growing ever more complex, and demands research that is bigger in scale, more collaborative and multi-disciplinary than ever before. This cutting-edge volume provides an accessible introduction to innovative digital social research tools and methods that harness this 'data deluge' and successfully tackle key research challenges. Contributions from leading international researchers cover topics such as: Qualitative, quantitative and mixed methods research; Data management; Social media and social network analysis; Modeling and simulation; Survey methods; Visualizing social data; Ethics and e-research. The future of social research in the digital age. This vibrant introduction to innovative digital research methods is essential reading for anyone conducting social research today.